2021
DOI: 10.1108/maj-04-2020-2622
|View full text |Cite
|
Sign up to set email alerts
|

Audit committee characteristics and bank performance: evidence from India

Abstract: Purpose This study aims to investigate the impact of various audit committee (AC) characteristics on the performance of Indian commercial banks. Additionally, it also analyses the non-linear relationship of AC size and AC chairman tenure with bank performance. Design/methodology/approach A panel data approach has been used in this study. The authors have used the fixed-effect estimation technique to examine the relationship between AC characteristics and bank performance during the period 2009–2010 to 2016–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 120 publications
0
15
0
8
Order By: Relevance
“…However, it has an insignificant role in determining asset quality. Gupta and Mahakud [ 86 ] assessed the impact of chief executive officers’ personal characteristics on the performance of Indian commercial banks. The results concluded that CEO duality and professional qualification in the finance stream have a positive and significant effect on banks’ performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has an insignificant role in determining asset quality. Gupta and Mahakud [ 86 ] assessed the impact of chief executive officers’ personal characteristics on the performance of Indian commercial banks. The results concluded that CEO duality and professional qualification in the finance stream have a positive and significant effect on banks’ performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mayur and Saravanan [ 88 ] showed no relationship between board composition and performance. Gupta and Mahakud [ 86 ] concluded that CEO duality and the professional qualification of CEOs in finance have a positive and significant effect on Indian banks’ performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Selain Indonesia telah banyak negara-negara lain yang baru-baru ini juga memfokuskan penelitian terkait dengan karakteristik yang melekat dalam kepengurusan AC diantaranya Palestina (Musallam, 2020), Bahrain (Oudat et al, 2021), Bangladesh (Fariha et al, 2021), India (Gupta & Mahakud, 2021) dan Ingris (McLaughlin et al, 2021). Kemudian, terdapat juga sebuah penelitian yang mencoba penelitian secara global serta mengkomparasikan antara bank syariah dan bank konvensional yaitu dilakukan oleh (Haddad et al, 2021).…”
Section: Pendahuluanunclassified
“…independen maka kinerja bank akan meningka karena anggota yang independen dipercaya dapat meningkatkan efektifitas pada ssaat melakukan evaluasi dan pengawasan. ACID di IB sejalan dengan penelitian (Gupta & Mahakud, 2021) yang menyatakan bahwa anggota independen lebih baik dari pada anggota yang berafiliasi. Begitu juga dengan (Ashari & Krismiaji, 2019) serta (Haddad et al, 2021) yang beranggapan independensi AC akan mengarahkan kinerja perusahaan jauh lebih baik.…”
Section: Model Strukturunclassified
See 1 more Smart Citation